Efeito preventivo da estimulação elétrica nervosa transcutânea (TENS) na dor muscular tardia em indivíduos destreinados - Pereira, Thaís Alves Barreto (2018)
Introduction: Delayed onset muscle soreness (DOMS) induced is characterized by muscle soreness, pain to movement and reduction of functionality. TENS has been shown to be effective in reducing pain severity associated with improved function, such as reduced fatigue and increased exercise tolerance. However, no study evaluated the ability of TENS, when applied prior to the painful process, to prevent DOMS and improve performance. Aims: evaluated the immediated effects of preventive TENS on pain and performance in DOMS of untrained individuals. Methods: Untrained individuals were included to perform DOMS protocol with functional push and pull movements. Volunteers were proportionally divided into: active TENS performed before DOMS protocol and placebo TENS. Volunteers were evaluated before exercise, reassessed immediately after and 24h after the intensity of pain, muscle fatigue, pressure pain threshold (PPT), muscle power, physical tolerance, temporal summation (TS), conditioned pain modulation (CPM) and body temperature. A reassessment of all variables measured after 24 hours of DOMS. For statistical analysis, the paired and independent T tests, Mann-Whitney, Wilcoxon and one-way ANOVA were used. Results: 44 volunteers were included in the project. It was found that the physical tolerance to rowing exercise in the immediate re-evaluation of the active TENS group (18.27 ± 5.27, 95% CI: 16.21 to 24) was significantly higher in comparison to the placebo TENS group (15.51 ± 6.21, p = 0.03, 95% CI: 13.32 to 18.93). The number of repetitions decreased in each series performed in both groups (p <0.05), but was significantly higher in the 5th series of the row exercise in the active TENS group (2.86 ± 1.24, 95% CI: 2, 34 to 3.38) compared to the placebo TENS group (1.81 ± 0.79, p = 0.001, 95% CI: 1.55 to 2.27). In both groups, there was an increase in the pain intensity at rest in the immediate re-evaluation (active TENS: p = 0.001, 95% CI 1.55 to 3.87, placebo TENS: p = 0.001, 95% CI: 1.18 to 3,24) and of movement in each exercise series (p <0.05), but without differences between groups. The same occurred for fatigue at rest (active TENS: p = 0.002, 95% CI: 4.61 to 4.91, TENS placebo: p = 0.001, 95% CI: 3.05 to 5.46), and on the move (p <0.05). In the MCD and ST variables, we observed the phenomenon of pain inhibition and pain summation (p <0.05), respectively, but there was no difference between the groups. Muscle power was lower in immediate reassessment in both groups at immediate reassessment (active TENS: p = 0.01, 95% CI: 207.01 to 287.11, TENS placebo: p = 0.001, 95% CI: 198.41 to 282.85), without recovery in the 24-h reevaluation and without significant difference between the groups. In the thermography, a statistically significant difference was found in the pectoralis major temperature between the groups (p = 0.04), and in the active TENS group there was no change in the temperature between the moments of evaluation and in the TENS placebo group there was a decrease in the reassessment immediate (p = 0.01, 32.36 to 33.70). Conclusion: Our results suggest the use of TENS in a preventive way to improve physical performance in the presence of DMT, without the increase of pain and fatigue beyond that expected.